Novel antiangiogenic peptide targeted therapeutic nanosystem for non-small-cell lung carcinoma - Ngema, Lindokuhle Malibongwe (University of the Witwatersrand, Johannesburg, 2023)
Lung cancer is the leading cause of cancer deaths globally, with nearly 1.8 million deaths and 2.2 million incidences recorded annually. Primarily, non-small-cell lung carcinoma (NSCLC) is the most commonly diagnosed type of lung cancer, which makes up approximately 85% of all reported lung cancer cases. Currently, the management of NSCLC is a global challenge, and although, various treatment protocols are available, such as surgery, radiotherapy, and chemotherapy, the survival outcomes remain poor. Combination chemotherapy is the current first-line treatment for NSCLC, however, it presents with a myriad of drawbacks, including non-specificity, high dosage, and detrimental side effects, resulting in patients intolerability to the regimen. Consequently, a new therapeutic approach is greatly needed and warrants the design of biocompatible targeted drug delivery nanosystems that can halt tumor proliferation and metastasis by targeting key molecules and deliver drugs directly to tumors, with limited side effects and toxicity to healthy cells. Tumor targeted drug delivery nanosystems such as magnetic nanoparticles (MNPs) modified with biomolecules and functionalized with homing peptides are of great interest for potential application as a potent nanomedicine in NSCLC management. Accordingly, the present study set to develop novel targeted paclitaxel (PTX) delivery nanosystems from the amenable superparamagnetic iron oxide nanoparticles (SPIONs) coated with trans-10,cis-12 conjugated linoleic acid (10E, 12Z) and functionalized with either a vascular endothelial growth factor receptor (VEGFR) binding or a matrix metalloproteinase 2 (MMP-2) binding peptide, for specific delivery of PTX to VEGFR and MMP-2 expressing NSCLC tumors. A preceding nanosystem without the peptides (CLA-coated PTX-SPIONs) was originally fabricated as proof of concept for the application of 10E, 12Z CLA as a surface coating and drug partitioning biomolecule. CLA-coated PTX-SPIONs exhibited a spherical shape, with an average particle size and zeta potential of 96.5 ± 0.6 nm and −27.3 ± 1.9 mV, respectively. The nanosystem had a drug loading efficiency of 98.5% and demonstrated a sustained site-specific in vitro release of PTX over 24 h (i.e., 94% at pH 6.8 mimicking the tumor microenvironment). Enhanced anti-proliferative activity was also observed with the CLA-coated PTX-SPIONs against a lung adenocarcinoma (A549) cell line after 72 h, with a recorded cell viability of 17.1%. Thereafter, the fabricated nanosystem was optimised for direct tumor-targeting by functionalization with HRH or CTT peptides, to give CLA-coated PTX-SPIONs@HRH and CLA-coated PTX-SPIONs@CTT. A new design methodology was established for the tandem surface functionalization of CLA-coated PTX-SPIONs with the antiangiogenic peptides, via coupling reactions. A series of robust nanotechnological techniques were employed for pertinent physicochemical characterization, in vitro evaluation of drug release, anti-proliferative activity, and quantification of VEGF-A and MMP-2 levels. Meanwhile, in vivo testing was carried out on a lung tumor xenograft mouse model. Both nanosystems exhibited a marked cellular uptake and internalization by A549 cells, and CLA-coated PTX-SPIONs@HRH significantly reduced secretion levels of VEGF-A in human dermal microvascular endothelial cells (HMEC-1) from 46.9 pg/mL to 35.6 pg/mL, meanwhile CLA-coated PTX-SPIONs@CTT significantly inhibited MMP-2 secretion by almost 70% , indicating specific anti-MMP-2 activity. A 76.6% and 69.7 % tumor regression was observed in a lung tumor xenograft mouse model treated with CLA-coated PTX SPIONS@HRH and CLA-coated PTX-SPIONs@CTT, respectively, demonstrating tumor targetability and angiogenesis inhibition. Lastly, the pharmacokinetics (PK) evaluation revealed that both nanosystems prolonged the half-life of PTX and circulation time in vivo. In essence, potent antiangiogenic tumor-targeted PTX delivery nanosystems were successfully fabricated, and the obtained results suggest potential application of CLA-coated PTX SPIONs@HRH and CLA-coated PTX-SPIONs@CTT for effective management of NSCLC.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Superparamagnetic iron oxide nanoparticles; Conjugated linoleic acid; Paclitaxel; Angiogenesis; HRH; CTT; Nanomedicine; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education